La carrière Rhéaume 1909-1937 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Carrière; Rosemont

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Crawford; Alexander

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n27 Translators: _:n62469
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
issued: 2022-21-00
Keywords: Saint-Jean-Baptiste (village); Villages

TRUDEAU, JOSEPH-CHARLES-ÉMILE - English, John (Dictionnaire biographique du Canada, 2022)

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-23-00
Keywords: Logement

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n95 Translators: _:n62402
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n139 Translators: _:n62391
Keywords: Hôtellerie; Marchés

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)